HER Tyrosine Kinase Family and Rhabdomyosarcoma: Role in Onset and Targeted Therapy - De Giovanni, Carla (Cells, 2021)
Rhabdomyosarcomas (RMS) are tumors of the skeletal muscle lineage. Two main features allow for distinction between subtypes: morphology and presence/absence of a translocation between the PAX3 (or PAX7) and FOXO1 genes. The two main subtypes are fusion-positive alveolar RMS (ARMS) and fusion-negative embryonal RMS (ERMS). This review will focus on the role of receptor tyrosine kinases of the human epidermal growth factor receptor (EGFR) family that is comprised EGFR itself, HER2, HER3 and HER4 in RMS onset and the potential therapeutic targeting of receptor tyrosine kinases. EGFR is highly expressed by ERMS tumors and cell lines, in some cases contributing to tumor growth. If not mutated, HER2 is not directly involved in control of RMS cell growth but can be expressed at significant levels. A minority of ERMS carries a HER2 mutation with driving activity on tumor growth. HER3 is frequently overexpressed by RMS and can play a role in the residual myogenic differentiation ability and in resistance to signaling-directed therapy. HER family members could be exploited for therapeutic approaches in two ways: blocking the HER member (playing a driving role for tumor growth with antibodies or inhibitors) and targeting expressed HER members to vehiculate toxins or immune effectors.